2008
DOI: 10.1161/atvbaha.107.150474
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion Mechanisms in Platelets

Abstract: Abstract-At sites of vascular injury, platelets come into contact with the subendothelial extracellular matrix which triggers their activation and the formation of a hemostatic plug. This process is crucial for normal hemostasis, but may also lead to pathological thrombus formation causing diseases such as myocardial infarction or stroke. The initial capture of flowing platelets is mediated by the interaction of the glycoprotein (GP) Ib-V-IX complex with von Willebrand factor (vWF) immobilized on exposed colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
434
0
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 518 publications
(478 citation statements)
references
References 119 publications
(114 reference statements)
4
434
0
16
Order By: Relevance
“…Here, we confirm by intravital microscopy that platelet depletion results in significantly decreased melanoma cell adhesion to the vascular wall in vivo, demonstrating an interaction of melanoma cells with platelets in vivo. Once adherent to the vessel wall, such as after endothelial injury, the platelet fibrinogen receptor GPIIb/IIIa becomes activated and contributes to thrombus formation and wound healing (3,59). Interestingly, we observed that inhibition of GPIIb/IIIa resulted in both the reduced adhesion of melanoma cells to immobilized platelets and the reduced adhesion to endothelial cells under shear flow conditions in the presence of platelets.…”
Section: Discussionmentioning
confidence: 80%
“…Here, we confirm by intravital microscopy that platelet depletion results in significantly decreased melanoma cell adhesion to the vascular wall in vivo, demonstrating an interaction of melanoma cells with platelets in vivo. Once adherent to the vessel wall, such as after endothelial injury, the platelet fibrinogen receptor GPIIb/IIIa becomes activated and contributes to thrombus formation and wound healing (3,59). Interestingly, we observed that inhibition of GPIIb/IIIa resulted in both the reduced adhesion of melanoma cells to immobilized platelets and the reduced adhesion to endothelial cells under shear flow conditions in the presence of platelets.…”
Section: Discussionmentioning
confidence: 80%
“…1,2 In contrast, uncontrolled platelet activation can induce acute vessel occlusion, leading to myocardial infarction or stroke at areas of atherosclerotic plaque rupture. 3,4 Platelet activation and thrombus formation is a multistage process that involves different signaling pathways to trigger platelet shape change, integrin activation, and degranulation. 4,5 The signaling pathways converge in the activation of phospholipase C (PLC), leading to the formation of inositol 1,4,5-triphosphate (IP 3 ) and diacylglycerol.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors bind to specific platelet receptors and regulate signaling pathways, which promote or inhibit platelet adhesion, aggregation, and secretion. In vivo, circulating platelets are continually exposed to a variety of activating factors including collagen, fibrinogen, ADP, von Willebrand Factor (vWF), thrombin, and thromboxane (3)(4)(5), as well as inhibitory factors such as endothelial-derived nitric oxide (NO), prostacyclin (PG-I 2 ), and ADPase (3,(5)(6). A strong equilibrium between the two opposing processes of platelet stimulation and inhibition is thought to be essential for normal platelet and vascular function.…”
mentioning
confidence: 99%
“…In the initial steps of platelet activation, the platelet receptor glycoproteins (GP) 3 1b and GPVI interact with extracellular matrix (ECM) proteins, causing platelets to tether and roll on the injured endothelium or subendothelial ECM (5). Stimulation of these receptors triggers intracellular signaling cascades that activate integrin ␣IIb␤3 and induce the release of secondary mediators like ADP and thromboxane A 2 (TXA 2 ), leading to full platelet activation and thrombus formation.…”
mentioning
confidence: 99%